Wavelet transformation of mode shape difference function for structural damage location identification. - Poudel, Upendra P. (Earthquake engineering & structural dynamics.)
In this paper, a new approach to structural damage detection is presented using mode shape difference between the reference and damage states. In order to capture and display the signal of damage, wavelet transformation is performed upon the mode shape difference function. Results show that this presentation of signal is effective for damage detection. Furthermore, practical aspects of damage identification are investigated, including understanding and using the frequency contents of the mode shape difference function, the mother wavelet function and the resulting wavelet coefficients due to the band-limited filtering of wavelet transformation. This proposition is experimented. Results are assertive of the proposed concept.